Pengaruh Sustainability Report Disclosure, Good Corporate Governance dan Kinerja Keuangan terhadap Nilai Perusahaan pada Perusahaan Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia - Salma Dewi Ambarsari; Titiek Rachmawati (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
The purpose of this study is to examinehow survival reports, good corporate governance, andfinancial performance affect company value in the mining sector in2022–t2024. This study involved 65 companies in themining industry from 2022–2024. This research is quantitative in nature. For this research, purposive sampling was used, which means that the samplewas selected based on predetermined standards. Thus, 15companies were selected as the research sample. The secondary data usedin this study came from the annual reports of the companies that were theresearch sample and the official website of the Indonesia Stock Exchange (IDX). The analysis methodused the SPSS 26 computer program. The results showed thatsustainability report disclosure and good corporate governance did notaffect company value; however, financial performance significantly affectedcompany value.